Manejo agronómico del cultivo de guanábana (Annona muricata L.), en el Ecuador - Rochina Cambo, Sonia Yajaira (2022)
Soursop has begun to develop in recent years, due to its great acceptance in international markets, offering new flavors and dietary range, in addition to therapeutic qualities of exquisite health benefits. The agronomic management of the soursop crop begins with planting, maintenance processes such as fertilization, pest, disease and weed control, which must be carried out in a timely manner until the closing of the crop. Taking into account that, in the first years of development, the trees tend to grow rapidly. The information obtained was carried out through the technique of analysis, synthesis and summary, so that the reader can learn about the agronomic management of the soursop crop (Annona muricata L.) in Ecuador. From the above, it was determined that the soursop crop is highly appreciated for its high commercial value, offering new flavors and dietary range with health benefits. The agronomic management of the soursop crop is made up of different activities that allow for adequate production and high fruit quality. The main activities include: propagation, crop establishment, weed management, fertilization, irrigation, pruning, insect, pest and disease control, and harvesting. Soursop is a commercial tropical fruit with a high yield potential, which is conditioned by the agronomic management of the crop from planting to harvesting. In Ecuador there are several soursop producing regions, but the main ones are: Guayaquil and Santa Elena (coast), where it is expected that there are 120 ha of soursop cultivation, there are also plantations in other sectors of the coast that include: Manabí, Esmeraldas, Santo Domingo and El Oro. In the Ecuadorian Oriente, soursop plantations are located in: Pastaza and Napo.